Job Rotation & Its Impact on employees’ Performance: An Empirical Study among Employees at Red Sea University, Sudan - Al.Beisani Al.Nabulsi Yousif Al.Ibed, Mohammed Omer Idris Salih, (International Journal of Scientific Research and Management (IJSRM), 2017)
This study aims to identify the employees view about job rotation through dimensions (benefits, disadvantages &obstacles)and how it is effects on their performance at Red Sea university in Sudan, Also know the relationship between employees, performance and years of experience, The results of study showed there is no statistically significant relationship between Job Rotation and Employees performance At Red Sea University. Because there are no relations between Job rotation variables (Benefits, Barriers &Disadvantages) &Employees performance (significant>0.05) ,But The statistical results of Chi-Square showed that there is statistically relation between Years of experience & Job Rotation (significant